Inflammation induced by incomplete radiofrequency ablation accelerates tumor progression and hinders PD-1 immunotherapy - Liangrong Shi (Nature Portfolio, 2019)
Radiofrequency ablation is used to treat metastatic colorectal cancer. In this study, the authors show that incomplete ablation of tumours results in metastases and show in mouse models that the chemokine CCL2 recruits myeloid cells to the partially ablated tumours, which can block T cell function.